2019
DOI: 10.1111/tpj.14518
|View full text |Cite
|
Sign up to set email alerts
|

The H3 histone chaperone NASPSIM3 escorts CenH3 in Arabidopsis

Abstract: SummaryCentromeres define the chromosomal position where kinetochores form to link the chromosome to microtubules during mitosis and meiosis. Centromere identity is determined by incorporation of a specific histone H3 variant termed CenH3. As for other histones, escort and deposition of CenH3 must be ensured by histone chaperones, which handle the non‐nucleosomal CenH3 pool and replenish CenH3 chromatin in dividing cells. Here, we show that the Arabidopsis orthologue of the mammalian NUCLEAR AUTOANTIGENIC SPER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 60 publications
1
48
0
Order By: Relevance
“…In many species, a dedicated CENP-A chaperone has been identified that performs this function. Human cells use HJURP [ 107 , 108 ] and RbAp48 [ 109 ], fruit flies use CAL1 [ 110 ], fission and budding yeast uses SCM3 [ 111 , 112 , 113 , 114 ], the holocentric roundworm Caenorhabditis elegans uses RbAp46/48 LIN-53 [ 115 ], and Arabidopsis thaliana uses NASP SIM3 [ 116 ]. Although knock-down of fruit fly 359-bp satellite RNA resulted in reduced levels of CAL1 at the centromere [ 51 ], HJURP has been shown to directly interact with α-satellite lncRNAs [ 21 ].…”
Section: Functions Of Centromeric Transcriptionmentioning
confidence: 99%
“…In many species, a dedicated CENP-A chaperone has been identified that performs this function. Human cells use HJURP [ 107 , 108 ] and RbAp48 [ 109 ], fruit flies use CAL1 [ 110 ], fission and budding yeast uses SCM3 [ 111 , 112 , 113 , 114 ], the holocentric roundworm Caenorhabditis elegans uses RbAp46/48 LIN-53 [ 115 ], and Arabidopsis thaliana uses NASP SIM3 [ 116 ]. Although knock-down of fruit fly 359-bp satellite RNA resulted in reduced levels of CAL1 at the centromere [ 51 ], HJURP has been shown to directly interact with α-satellite lncRNAs [ 21 ].…”
Section: Functions Of Centromeric Transcriptionmentioning
confidence: 99%
“…Evidence in plants is largely missing, and only indirect indications for a role in CENH3 chaperone function are available. For instance, the interaction of NASP with both CENH3 and H3.1/H3.3 has been demonstrated ( Le Goff et al , 2020 ). HFDs of H3s and CENH3 show 50–60% sequence similarity within the same species ( Talbert and Henikoff, 2010 ).…”
Section: Candidate Cenh3-interacting Proteins With Functions Related mentioning
confidence: 99%
“…An ortholog of NASP identified in A. thaliana shows H3 chaperone activity ( Maksimov et al , 2016 ). NASP also binds CENH3, and NASP down-regulation impairs the loading of CENH3 at the centromeres ( Le Goff et al , 2020 ). An HJURP-like CENH3-selective chaperone has hitherto not been identified in plants.…”
Section: Introduction: Cenh3 As a Core Component Of Centromeresmentioning
confidence: 99%
“…Inna Lermontova (Gatersleben, Germany) reported on the collaborative effort to search for histone CenH3 interactors and the identification of the plant homologue of NUCLEAR AUTOANTIGENIC SPERM PROTEIN (NASP) as a CenH3 binding protein. Previously shown to bind histone H3 monomers or H3-H4 dimers (Maksimov et al, 2016), the nuclear NASP protein interacts both with the N-terminal tail as well as with the histone fold domain of CenH3 and reduced NASP expression negatively affects CenH3 levels, suggesting that NASP functions as a CenH3 escort protein (Le Goff et al, 2019).…”
Section: Session 3: Making Variations Of Chromatin-incorporating Bricmentioning
confidence: 99%